Optimalisasi Audit Siklus Persediaan Dalam Menangkal Risiko Kecurangan Dan Menjamin Keandalan Informasi Keuangan Perusahaan - Dwi Aulia Afrizka; Rahmah Nur Aqilah; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
Inventory represents one of the most significant assets in a company and is highly vulnerable to fraud and material misstatement, which may undermine the reliability of financial information. This study aims to analyze the optimization of inventory cycle audits in mitigating fraud risks and ensuring the reliability of corporate financial information. The research employs a qualitative descriptive approach through an in-depth literature review of prior studies, auditing standards, and accounting theories related to inventory auditing, internal control, and audit technology. The findings indicate that an effective inventory audit cycle, supported by strong internal controls, risk-based audit approaches, and data analytics, significantly enhances the accuracy and reliability of inventory records. Proper audit procedures, including physical observation, valuation testing, and stock opname supervision, play a crucial role in detecting irregularities and preventing fraud. Furthermore, the integration of audit technology improves audit efficiency and strengthens assurance over financial reporting. The study concludes that optimizing inventory cycle audits contributes not only to fraud prevention but also to improving financial transparency, accountability, and decision-making quality within organizations.